Antistatic polyethylene foam composite material and preparation method thereof
Patent Information
- Application Number
- CN202611434125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本发明的目的在于:提供了一种抗静电聚乙烯发泡棉复合材料及其制备方法,解决了目前聚乙烯发泡棉复合材料通过抗静电剂迁移至材料表面并吸附环境水分形成导电水膜,起到抗静电作用,具有湿度限制及表层磨损导致的使用周期短的问题
[0025]1.本发明在发泡材料的基体中加入不依靠迁移及吸湿的抗静电剂,通过导电组分锚固在主体结构中形成导电网络,起到抗静电的作用;导电网络的主要成分为TEMPO氧化纤维素纳米纤维/氨基化MXene/超支化星状聚离子液体预组装复合物,其中,氨基化MXene为导电骨架,TEMPO氧化纤维素纳米纤维提高导电网络的韧性,避免主体发泡膨胀拉断导电网络,超支化星状聚离子液体在与MXene协同加强导电作用的情况下,增强整体强度,可抑制泡孔膨胀对导电组分的推挤,因为导电组分在推挤过程中容易出现明显运移,导致导电不均匀,抗静电效果差的问题;
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer foaming material technology, and relates to an antistatic polyethylene foam composite material and its preparation method. Background Technology
[0002] Polyethylene foam and chemically cross-linked polyethylene foam are widely used in the transport packaging of electronic components due to their lightweight and excellent cushioning properties. Electronic components are prone to accumulating static electricity during transport and handling due to friction. Electrostatic discharge can cause irreversible failures such as chip breakdown and hard drive head damage. Therefore, this type of packaging must possess stable and reliable antistatic properties.
[0003] The current mainstream antistatic solution in the industry is to add a migratory antistatic agent to the polyethylene foam system. The antistatic mechanism is that the antistatic agent migrates to the material surface and adsorbs environmental moisture to form a conductive water film. This approach has the following drawbacks: the antistatic effect is highly dependent on the ambient humidity. Even if the performance meets the standard initially, it may completely lose its antistatic effect within hours to days in a continuous low humidity environment; the surface is easily worn, the antistatic performance decays quickly, and the service life is short. Summary of the Invention
[0004] The purpose of this invention is to provide an antistatic polyethylene foam composite material and its preparation method, which solves the problems of current polyethylene foam composite materials where the antistatic agent migrates to the material surface and adsorbs environmental moisture to form a conductive water film to play an antistatic role, but has the problems of humidity limitation and short service life caused by surface wear.
[0005] The technical solution adopted in this invention is as follows:
[0006] An antistatic polyethylene foam composite material comprises the following components in parts by weight: 45-50 parts base material, 6-8 parts masterbatch A and 45-50 parts masterbatch B;
[0007] Independently calculated, the base material comprises the following components in parts by weight: 100 parts linear low-density polyethylene, 25-30 parts AC foaming agent, 1.6-1.8 parts dicumyl peroxide, 2.0-2.5 parts talc, and 1.5-2.0 parts zinc stearate;
[0008] Independently calculated, the masterbatch A comprises the following components in parts by weight: 100 parts ethylene-acrylic acid copolymer, 35-38 parts TEMPO oxidized cellulose nanofibers / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite.
[0009] Independently calculated, the masterbatch B comprises the following components in parts by weight: 8-10 parts of glycidyl methacrylate-grafted ethylene octene copolymer modified with diamino F127, and 100 parts of high-pressure polyethylene.
[0010] Furthermore, the mass ratio of TEMPO oxidized cellulose nanofibers, aminated MXene, and hyperbranched star-shaped polyionic liquid in the TEMPO oxidized cellulose nanofibers / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite is 1:2:1.3.
[0011] Furthermore, the TEMPO oxidized cellulose nanofibers were prepared using bleached softwood pulp as the fiber raw material in a TEMPO-NaClO-NaBr oxidation system. The carboxyl group molar concentration of the oxidized cellulose nanofibers reached 0.6~0.7 mmol.g. -1 .
[0012] Further, the aminated MXene is a polyaminopolyether methylenephosphonic acid modified MXene, which is prepared by the following method: a 1.5 wt% polyaminopolyether methylenephosphonic acid solution is added dropwise at a rate of 0.3–0.5 mL / min to a 5 mg / mL monolayer Ti3C2MXene dispersion under stirring at 500 rpm. The amount of polyaminopolyether methylenephosphonic acid used is 23% of the mass of the monolayer Ti3C2MXene. The pH is adjusted to 4.5, stirred at 50°C for 6 hours, centrifuged, washed with deionized water, and vacuum dried at 40°C to obtain the polyaminopolyether methylenephosphonic acid modified MXene.
[0013] Furthermore, the hyperbranched star-shaped polyionic liquid is a hyperbranched star-shaped polyionic liquid HPG-PVBMM with a branching degree of 0.6 and a molecular weight of 4600 as the core and polyionic liquid as the arms. + Cl - .
[0014] Furthermore, the TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was prepared by the following method: aminated MXene was dispersed in deionized water, and the hyperbranched star-shaped polyionic liquid HPG-PVBMM was added. + Cl - The aqueous solution was stirred at 40–60 °C for 2–4 h, and then TEMPO oxidized cellulose nanofiber aqueous dispersion was added. The pH was adjusted to 4–5, and the mixture was stirred for 0.5–2 h. After freeze-drying, a TEMPO oxidized cellulose nanofiber / amino-MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was obtained.
[0015] Furthermore, the ethylene-acrylic acid copolymer is a copolymer of ethylene and acrylic acid, and the content of acrylic acid is 9.5 wt%.
[0016] Further, the glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 terminal amino groups was prepared by the following method: the glycidyl methacrylate-grafted ethylene octene copolymer was dissolved in toluene to prepare a 10 wt% solution, and heated to 80°C; the glycidyl methacrylate-grafted ethylene octene copolymer solution was slowly added dropwise to the toluene / isopropanol mixed solvent; wherein the molar ratio of the amino group of the glycidyl methacrylate-grafted ethylene octene copolymer to the epoxy group of the glycidyl methacrylate-grafted ethylene octene copolymer was 1:2 to 1:4; the reaction was stirred at 80°C for 4 to 6 hours; the solvent was removed by rotary evaporation to obtain the glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 terminal amino groups.
[0017] Furthermore, the melt index of the high-pressure polyethylene is 2 g / 10 min; the melt index of the linear low-density polyethylene is 1.9 g / 10 min.
[0018] A method for preparing an antistatic polyethylene foam composite material includes the following steps:
[0019] S1. Preparation of Masterbatch A: Ethylene-acrylic acid copolymer and TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite are added to a twin-screw extruder and extruded and granulated at 155±5℃ to obtain Masterbatch A;
[0020] S2. Preparation of Masterbatch B: High-pressure polyethylene and glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 amino-terminated ends are mixed evenly and granulated by twin-screw extrusion at an extrusion temperature of 170±5℃ to obtain Masterbatch B.
[0021] S3, Base Material: Linear low-density polyethylene, AC foaming agent, dicumyl peroxide, talc, and zinc stearate are all mixed at room temperature in a high-speed mixer to obtain the base material;
[0022] S4. Extrusion of masterbatch: Mix the base material, masterbatch A and masterbatch B evenly, feed them into a single screw extruder, and extrude them into masterbatch at 130°C.
[0023] S5. Foaming and crosslinking: The mother sheet is placed in a foaming furnace at 210-220℃ and heated for 8-12 minutes, then cooled and shaped to obtain an antistatic polyethylene foam composite material.
[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0025] 1. This invention incorporates an antistatic agent that does not rely on migration or moisture absorption into the matrix of a foamed material. This agent forms a conductive network by anchoring conductive components within the main structure, thus achieving an antistatic effect. The main components of the conductive network are a pre-assembled composite of TEMPO oxidized cellulose nanofibers / aminated MXene / hyperbranched star-shaped polyionic liquid. Aminated MXene serves as the conductive framework, while TEMPO oxidized cellulose nanofibers enhance the toughness of the conductive network, preventing the foam expansion from breaking the network. The hyperbranched star-shaped polyionic liquid, in synergy with MXene to strengthen conductivity, enhances the overall strength and inhibits the pushing of conductive components by cell expansion. This is because conductive components are prone to significant migration during the pushing process, leading to uneven conductivity and poor antistatic effect.
[0026] 2. In this invention, glycidyl methacrylate grafted with ethylene octene and modified with F127 at both ends is added to form an interfacial transition layer between the conductive component and the polyethylene matrix, which improves the compatibility between the conductive component and the polyethylene matrix and reduces the risk of macrosegregation of the conductive component due to interfacial debonding when the foam wall is stretched during the foaming process. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort, wherein:
[0028] Figure 1 , Figure 2 This is a physical image of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0030] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0031] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0032] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0033] The preparation of the key components used in the following embodiments of the present invention is described below:
[0034] Preparation Example 1: TEMPO oxidized cellulose nanofibers were prepared using existing techniques.
[0035] TEMPO-oxidized cellulose nanofibers are prepared from bleached softwood pulp using a TEMPO-NaClO-NaBr oxidation system. The oxidized cellulose nanofibers have a carboxyl group molar concentration of 0.67 mmol / g. -1 .
[0036] Preparation Example 2: Preparation of Aminated MXene
[0037] Aminated MXene is a polyaminopolyether methylenephosphonic acid modified MXene, which is prepared by the following method: a 1.5 wt% polyaminopolyether methylenephosphonic acid solution is added dropwise at a rate of 0.4 mL / min to a 5 mg / mL monolayer Ti3C2MXene dispersion under stirring at 500 rpm. The amount of polyaminopolyether methylenephosphonic acid used is 23% of the mass of the monolayer Ti3C2MXene. The pH is adjusted to 4.5, stirred at 50℃ for 6 hours, centrifuged, washed with deionized water, and vacuum dried at 40℃ to obtain polyaminopolyether methylenephosphonic acid modified MXene.
[0038] Preparation Example 3: Hyperbranched star-shaped polyionic liquids were prepared using existing techniques.
[0039] The hyperbranched star-shaped polyionic liquid is HPG-PVBMM, a hyperbranched star-shaped polyionic liquid with a branching degree of 0.6 and a molecular weight of 4600 as the core and polyionic liquid as the arms. + Cl- (Hyperbranched star-shaped polyionic liquid HPG-PVBMM) + Cl - (This was prepared directly using existing methods, and will not be elaborated upon here).
[0040] Preparation Example 4: Based on the components obtained in Preparation Examples 1-3 above, a TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was prepared.
[0041] The TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was prepared by the following method: Aminated MXene was dispersed in deionized water at a solid-liquid ratio of 1 g: 100 mL to obtain an MXene dispersion. Hyperbranched star-shaped polyionic liquid HPG-PVBMM with a mass concentration of 1.5 wt% was then added to the MXene dispersion. + Cl - The aqueous solution was stirred at 50℃ for 4 h, and then a TEMPO oxidized cellulose nanofiber aqueous dispersion with a mass concentration of 0.3 wt% was added. The pH was adjusted to 4.5, and the mixture was stirred for 1.5 h. After freeze drying, a TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was obtained. The mass ratio of TEMPO oxidized cellulose nanofiber, aminated MXene and hyperbranched star-shaped polyionic liquid was 1:2:1.3.
[0042] Preparation Example 5: Preparation of glycidyl methacrylate-grafted ethylene octene copolymer modified with F127-terminated amino groups
[0043] The glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 (terminated with amino groups) was prepared by the following method: The glycidyl methacrylate-grafted ethylene octene copolymer was dissolved in toluene to prepare a 10 wt% solution, which was then heated to 80°C. The diamino group F127 was dissolved in a toluene / isopropanol mixture with a volume ratio of 4:1 to prepare an 8 wt% diamino group F127 solution. This solution was then slowly added dropwise to the glycidyl methacrylate-grafted ethylene octene copolymer solution. The molar ratio of the amino groups in the diamino group F127 to the epoxy groups in the glycidyl methacrylate-grafted ethylene octene copolymer was 1:4. The reaction was stirred at 80°C for 6 hours. The solvent was removed by rotary evaporation to obtain the glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 (terminated with amino groups). The glycidyl methacrylate-grafted ethylene octene copolymer was commercially available from a certain plastic raw material company, model SH035.
[0044] Component selection: The ethylene-acrylic acid copolymer described in the following examples is a copolymer of ethylene and acrylic acid, with an acrylic acid content of 9.5 wt%; the melt index of the high-pressure polyethylene is 2 g / 10 min; the melt index of the linear low-density polyethylene is 1.9 g / 10 min; all are commercially available components.
[0045] Example 1
[0046] This embodiment provides an antistatic polyethylene foam composite material, comprising the following components in parts by weight: 48 parts base material, 7 parts masterbatch A, and 48 parts masterbatch B;
[0047] Independently calculated, the base material comprises the following components in parts by weight: 100 parts linear low-density polyethylene, 28 parts AC foaming agent, 1.7 parts dicumyl peroxide, 2.3 parts talc, and 1.8 parts zinc stearate;
[0048] Independently calculated, the masterbatch A comprises the following components in parts by weight: 100 parts ethylene-acrylic acid copolymer, 37 parts TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite.
[0049] Independently calculated, the masterbatch B comprises the following components in parts by weight: 9 parts of glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 diamino groups and 100 parts of high-pressure polyethylene.
[0050] The preparation method of the above-mentioned antistatic polyethylene foam composite material includes the following steps:
[0051] S1. Preparation of Masterbatch A: Ethylene-acrylic acid copolymer and TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite are added to a twin-screw extruder and extruded and granulated at 155°C to obtain Masterbatch A;
[0052] S2. Preparation of Masterbatch B: High-pressure polyethylene and glycidyl methacrylate grafted ethylene octene copolymer modified with F127 amino-terminated polymer are mixed evenly and granulated by twin-screw extrusion at 170℃ to obtain Masterbatch B.
[0053] S3, Base Material: Linear low-density polyethylene, AC foaming agent, dicumyl peroxide, talc, and zinc stearate are all mixed at room temperature in a high-speed mixer to obtain the base material;
[0054] S4. Extrusion of masterbatch: Mix the base material, masterbatch A and masterbatch B evenly, feed them into a single screw extruder, and extrude them into masterbatch at 130°C.
[0055] S5. Foaming and crosslinking: The mother sheet is placed in a foaming oven at 220°C and heated for 10 minutes, then cooled and shaped to obtain an antistatic polyethylene foam composite material; the actual product prepared within the scope of Example 1 is shown in the figure below. Figure 1 , Figure 2 As shown, a uniformly distributed void structure is visible to the naked eye on both the surface and the sides.
[0056] Example 2
[0057] This embodiment differs from Embodiment 1 in that it provides an antistatic polyethylene foam composite material comprising the following components in parts by weight: 45 parts base material, 6 parts masterbatch A, and 45 parts masterbatch B; the rest are the same.
[0058] Example 3
[0059] This embodiment differs from Embodiment 1 in that it provides an antistatic polyethylene foam composite material comprising the following components in parts by weight: 50 parts base material, 8 parts masterbatch A, and 50 parts masterbatch B; the rest are the same.
[0060] Comparative Example 1
[0061] Based on Example 1, the difference from Example 1 is that the polyethylene foam composite material provided in this comparative example does not contain masterbatch A; otherwise, it is the same as Example 1.
[0062] Comparative Example 2
[0063] Based on Example 1, the difference from Example 1 is that the TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled complex in this comparative example masterbatch A is replaced with an equal amount of unmodified monolayer Ti3C2MXene, and the rest is the same as in Example 1.
[0064] Comparative Example 3
[0065] Based on Example 1, the difference from Example 1 is that the amino-modified MXene in the TEMPO oxidized cellulose nanofiber / amino-modified MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite in this comparative example masterbatch A is replaced with an equal amount of unmodified monolayer Ti3C2 MXene, and the rest is the same as in Example 1.
[0066] Comparative Example 4
[0067] Based on Example 1, the difference from Example 1 is that the pre-assembled complex of the comparative example masterbatch A does not include amino-modified MXene. The preparation method can be adapted to the method described in Example 1; the rest is the same as in Example 1.
[0068] Comparative Example 5
[0069] Based on Example 1, the difference from Example 1 is that the pre-assembled complex of the comparative masterbatch A does not include TEMPO oxidized cellulose nanofibers. The preparation method can be adapted to Example 1; the rest is the same as Example 1.
[0070] Comparative Example 6
[0071] Based on Example 1, the difference from Example 1 is that the pre-assembled complex of the comparative example masterbatch A does not include hyperbranched star-shaped polyionic liquid. The preparation method can be adapted to Example 1; the rest is the same as Example 1.
[0072] Comparative Example 7
[0073] Based on Example 1, the difference from Example 1 is that the TEMPO oxidized cellulose nanofibers, aminated MXene, and hyperbranched star-shaped polyionic liquid in this comparative example masterbatch A are not pre-assembled, and Example 4 is not performed; instead, the ethylene-acrylic acid copolymer, TEMPO oxidized cellulose nanofibers, aminated MXene, and hyperbranched star-shaped polyionic liquid are directly added to a twin-screw extruder and extruded and granulated at 155°C to obtain masterbatch A; the rest is the same as in Example 1.
[0074] Comparative Example 8
[0075] Based on Example 1, the difference from Example 1 is that the existing antistatic agent AC-1802 (bis(β-hydroxyethyl) stearamine) is used in an equal amount to replace the TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite in masterbatch A; the rest is the same as in Example 1.
[0076] Comparative Example 9
[0077] Based on Example 1, the difference from Example 1 is that in Masterbatch B, an equal amount of glycidyl methacrylate-grafted ethylene octene copolymer is used to replace the bi-terminated amino F127 modified product, and the rest is the same as in Example 1.
[0078] Experimental Example 1
[0079] Performance tests were conducted on the products of Examples 1-3 and Comparative Examples 1-9. The results are shown in Tables 1 and 2. The test items included:
[0080] Surface resistivity: Tested according to GB / T 1410. The samples were conditioned for 48 h in environments of 23℃ and 50%RH and 23℃ and 15%RH respectively. The average value was taken from 5 parallel samples in each test group.
[0081] Foaming ratio: Refer to standard GB / T 6343 to measure density and convert foaming ratio. The foaming ratio is calculated by measuring the density ratio before and after foaming. Foaming ratio = density of the parent sheet / density of the antistatic polyethylene foam composite material; the average value is obtained from 5 parallel samples in each test group.
[0082] Damp heat aging: Surface resistivity was remeasured after being placed at 70℃ and 50%RH for 168 h; the average value was taken from 5 parallel samples in each test group.
[0083] Compressive stress value: Refer to standard ASTM D1056-2007. Before testing, the specimen should be equilibrated for 24 hours at 23±2℃ and 50±5%RH. The specimen is compressed to 25% of its thickness and held for 20 seconds. The load value is read. Compressive stress = load value / specimen area. The average value is taken from 5 parallel specimens in each test group.
[0084] Triboelectric voltage: Referring to standard SJ / T 10694, a triboelectric device is used. A standard friction cloth (nylon) is used to unidirectionally rub the sample surface 100 times under constant pressure (e.g., 50 kPa) and speed (e.g., 0.1 m / s). A non-contact electrostatic voltmeter is used to measure the voltage induced by the friction trajectory within 10 seconds after the friction stops, at a distance of 1 cm from the sample surface. The test object is properly grounded. Three different points are tested for each sample, and the average value is taken. Five parallel samples are used in each test group to obtain the benchmark value. The test temperature is 20℃, and the relative humidity is 30%.
[0085] Tensile strength and elongation at break: Tested according to GB / T 6344, with a tensile rate of 500±50 mm / min, and 10 samples were tested in each group and the average value was taken.
[0086] Electrostatic voltage decay time: Refer to SJ / T 10694-2006, using an electrostatic decay tester (capable of outputting a DC voltage of not less than ±1000 V, with a total test circuit capacitance of 20 pF ± 2 pF including the charging plate, a system response time of not more than 0.2 s, and a system test accuracy of not less than ±10%). Cut the sample to a size smaller than the area of the charging plate, place it flat on the charging plate, and maintain good contact. After charging the sample to ground until the voltage stabilizes at +1000 V, ground the sample to discharge static electricity, and record the time required for the voltage to decay from +1000 V to +100 V (i.e., decay to 10% of the initial value). After the sample is destaticated, measure the time from -1000 V to -100 V using the same method, and take the larger value between the positive and negative polarities as the test result. The common acceptance criterion for antistatic packaging materials is a decay time <2 s, which is considered qualified. Measure 10 samples in each group and take the average value.
[0087] Table 1 Performance Test Results
[0088] Surface resistivity (Ω) at 50%RH Surface resistivity (Ω) at 15%RH Foaming ratio (times) After aging under damp heat at 50% RH (Ω) Example 1 <![CDATA[1.1×10 6 ]]> <![CDATA[2.5×10 6 ]]> 32 <![CDATA[3.2×10 7 ]]> Example 2 <![CDATA[1.5×10 6 ]]> <![CDATA[3.0×10 6 ]]> 32 <![CDATA[4.5×10 7 ]]> Example 3 <![CDATA[1.8×10 6 ]]> <![CDATA[4.2×10 6 ]]> 31 <![CDATA[4.8×10 7 ]]> Comparative Example 1 <![CDATA[2.5×10 13 ]]> <![CDATA[2.8×10 13 ]]> 28 <![CDATA[3.3×10 13 <!-- 6 -->]]> Comparative Example 2 <![CDATA[6.5×10 9 ]]> <![CDATA[8.2×10 9 ]]> 22 <![CDATA[9.5×10 9 ]]> Comparative Example 3 <![CDATA[2.1×10 7 ]]> <![CDATA[3.5×10 7 ]]> 26 <![CDATA[6.8×10 8 ]]> Comparative Example 4 <![CDATA[5.0×10 8 ]]> <![CDATA[2.1×10 11 ]]> 29 <![CDATA[9.3×10 8 ]]> Comparative Example 5 <![CDATA[4.2×10 7 ]]> <![CDATA[8.2×10 7 ]]> 25 <![CDATA[3.2×10 8 ]]> Comparative Example 6 <![CDATA[6.3×10 8 ]]> <![CDATA[9.6×10 8 ]]> 27 <![CDATA[5.0×10 9 ]]> Comparative Example 7 <![CDATA[3.3×10 8 ]]> <![CDATA[7.0×10 8 ]]> 25 <![CDATA[2.5×10 9 ]]> Comparative Example 8 <![CDATA[8.5×10 8 ]]> <![CDATA[7.9×10 11 ]]> 22 <![CDATA[6.3×10 12 ]]> Comparative Example 9 <![CDATA[9.0×10 6 ]]> <![CDATA[1.1×10 7 ]]> 30 <![CDATA[8.5×10 7 ]]>
[0089] Table 2 Performance Test Results
[0090] Compressive stress value (kPa) Triboelectric voltage (volts V) Tensile strength (MPa) Elongation at break (%) Electrostatic voltage decay time (s) Example 1 64 35 0.38 115 qualified Example 2 63 50 0.36 113 qualified Example 3 66 60 0.35 108 qualified Comparative Example 1 78 >2000 0.41 95 Unqualified Comparative Example 2 98 800 0.44 71 Unqualified Comparative Example 3 85 110 0.43 90 Unqualified Comparative Example 4 73 480 0.40 100 Unqualified Comparative Example 5 88 150 0.43 88 Unqualified Comparative Example 6 82 320 0.42 85 Unqualified Comparative Example 7 86 280 0.43 80 Unqualified Comparative Example 8 102 560 0.44 78 Unqualified Comparative Example 9 68 85 0.34 105 qualified
[0091] Experimental Example 2
[0092] The product prepared in Example 1 was subjected to SVHC and RoHS testing. The test results are shown in Table 3, and the results are compliant with the requirements.
[0093] SVHC testing: SVHCs are screened based on the European Chemicals Agency's (ECA) candidate list for authorization consideration (in accordance with EU Regulation 1907 / 2006 REACH); SVHCs are also screened based on the ECA's consultation list of potential SVHCs (in accordance with EU Regulation 1907 / 2006 REACH); potential undetermined SVHCs are screened; and potential SVHCs are screened based on the ECA's proposed list of SVHCs (in accordance with EU Regulation 1907 / 2006 REACH). An SVHC result ≤0.1% (w / w) is considered acceptable.
[0094] RoHS Testing: The content of lead, mercury, cadmium, hexavalent chromium, polybrominated biphenyls (PBBs), polybrominated diphenyl ethers (PBDEs), di(2-ethylhexyl) phthalate (DEHP), butyl benzyl phthalate (BBP), dibutyl phthalate (DBP), and diisobutyl phthalate (DIBP) as specified in Annex II of the EU RoHS Directive 2011 / 65 / EU (EU) 2015 / 863 was determined by reference to IEC 62321-4:2013+AMD1:2017, IEC 62321-5:2013, IEC 62321-7-2:2017, and IEC 62321-12:2023. Analysis was performed using ICP-OES / AAS, UV-Vis, and GC-MS; ND = Not detected (< method detection limit).
[0095] Table 3 Product Safety Testing
[0096] SVHC test results RoHS test results Example 1 All items passed. All items are ND
[0097] In summary, this application has successfully prepared a polyethylene foam composite material with antistatic properties that is not significantly dependent on moisture. Example 1 showed a surface resistivity of only 2.5 × 10⁻⁶ under low humidity conditions (15% RH). 6 Ω, still maintained at 10 after damp heat aging 7The electrostatic voltage is on the order of Ω; the static voltage is only 35 V, and the actual measured electrostatic decay time is about 0.5 s, which is far better than the acceptance criterion of 2 s; the results show that the conductive components form a stable conductive network, exhibiting good low humidity adaptability and long-term stability.
[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An antistatic polyethylene foam composite material, characterized in that: It includes the following components in parts by weight: 45-50 parts base material, 6-8 parts masterbatch A and 45-50 parts masterbatch B; Independently calculated, the base material comprises the following components in parts by weight: 100 parts linear low-density polyethylene, 25-30 parts AC foaming agent, 1.6-1.8 parts dicumyl peroxide, 2.0-2.5 parts talc, and 1.5-2.0 parts zinc stearate; Independently calculated, the masterbatch A comprises the following components in parts by weight: 100 parts ethylene-acrylic acid copolymer, 35-38 parts TEMPO oxidized cellulose nanofibers / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite. Independently calculated, the masterbatch B comprises the following components in parts by weight: 8-10 parts of glycidyl methacrylate-grafted ethylene octene copolymer modified with diamino F127, and 100 parts of high-pressure polyethylene.
2. The antistatic polyethylene foam composite material according to claim 1, characterized in that: The mass ratio of TEMPO oxidized cellulose nanofibers, amino-modified MXene, and hyperbranched star-shaped polyionic liquid in the pre-assembled composite of TEMPO oxidized cellulose nanofibers / amino-modified MXene / hyperbranched star-shaped polyionic liquid is 1:2:1.
3.
3. The antistatic polyethylene foam composite material according to claim 2, characterized in that: TEMPO-oxidized cellulose nanofibers are prepared from bleached softwood pulp using a TEMPO-NaClO-NaBr oxidation system. The oxidized cellulose nanofibers have a carboxyl group molar concentration of 0.6–0.7 mmol / g. -1 .
4. The antistatic polyethylene foam composite material according to claim 2, characterized in that: Aminated MXene is a polyaminopolyether methylenephosphonic acid modified MXene, which is prepared by the following method: a 1.5 wt% polyaminopolyether methylenephosphonic acid solution is added dropwise at a rate of 0.3–0.5 mL / min to a 5 mg / mL monolayer Ti3C2MXene dispersion under stirring at 500 rpm. The amount of polyaminopolyether methylenephosphonic acid used is 23% of the mass of the monolayer Ti3C2MXene. The pH is adjusted to 4.5, stirred at 50°C for 6 hours, centrifuged, washed with deionized water, and vacuum dried at 40°C to obtain polyaminopolyether methylenephosphonic acid modified MXene.
5. The antistatic polyethylene foam composite material according to claim 2, characterized in that: The hyperbranched star-shaped polyionic liquid is HPG-PVBMM, a hyperbranched star-shaped polyionic liquid with a branching degree of 0.6 and a molecular weight of 4600 as the core and polyionic liquid as the arms. + Cl - .
6. The antistatic polyethylene foam composite material according to claim 2, characterized in that: The TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was prepared by the following method: aminated MXene was dispersed in deionized water, and the hyperbranched star-shaped polyionic liquid HPG-PVBMM was added. + Cl - The aqueous solution was stirred at 40–60 °C for 2–4 h, and then TEMPO oxidized cellulose nanofiber aqueous dispersion was added. The pH was adjusted to 4–5, and the mixture was stirred for 0.5–2 h. After freeze-drying, a TEMPO oxidized cellulose nanofiber / amino-MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite was obtained.
7. The antistatic polyethylene foam composite material according to claim 1, characterized in that: The ethylene-acrylic acid copolymer is a copolymer of ethylene and acrylic acid, with an acrylic acid content of 9.5 wt%.
8. The antistatic polyethylene foam composite material according to claim 1, characterized in that: The glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 terminal amino groups was prepared by the following method: the glycidyl methacrylate-grafted ethylene octene copolymer was dissolved in toluene to prepare a 10 wt% solution, and heated to 80°C; the glycidyl methacrylate-grafted ethylene octene copolymer solution was slowly added dropwise to the toluene / isopropanol mixed solvent; wherein the molar ratio of the amino group of the glycidyl methacrylate-grafted ethylene octene copolymer to the epoxy group of the glycidyl methacrylate-grafted ethylene octene copolymer was 1:2 to 1:4; the reaction was stirred at 80°C for 4 to 6 hours; the solvent was removed by rotary evaporation to obtain the glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 terminal amino groups.
9. The antistatic polyethylene foam composite material according to claim 1, characterized in that: The melt index of the high-pressure polyethylene is 2 g / 10 min; the melt index of the linear low-density polyethylene is 1.9 g / 10 min.
10. A method for preparing an antistatic polyethylene foam composite material according to any one of claims 1-9, characterized in that: Includes the following steps: S1. Preparation of Masterbatch A: Ethylene-acrylic acid copolymer and TEMPO oxidized cellulose nanofiber / aminated MXene / hyperbranched star-shaped polyionic liquid pre-assembled composite are added to a twin-screw extruder and extruded and granulated at 155±5℃ to obtain Masterbatch A; S2. Preparation of Masterbatch B: High-pressure polyethylene and glycidyl methacrylate-grafted ethylene octene copolymer modified with F127 amino-terminated ends are mixed evenly and granulated by twin-screw extrusion at an extrusion temperature of 170±5℃ to obtain Masterbatch B. S3, Base Material: Linear low-density polyethylene, AC foaming agent, dicumyl peroxide, talc, and zinc stearate are all mixed at room temperature in a high-speed mixer to obtain the base material; S4. Extrusion of masterbatch: Mix the base material, masterbatch A and masterbatch B evenly, feed them into a single screw extruder, and extrude them into masterbatch at 130°C. S5. Foaming and crosslinking: The mother sheet is placed in a foaming furnace at 210-220℃ and heated for 8-12 minutes, then cooled and shaped to obtain an antistatic polyethylene foam composite material.